Exit Decisions in Mature Industries - Harrigan, Kathryn Rudie (Academy of Management Journal, 1982)
Measures of exit barriers and inducements to exit are constructed in a study of exits from nondeclining industries. Findings are contrasted with those from a study of exits within declining industries. The most significant factors influencing exit within mature, nondeclining industries were the presence of excess capacity and the apparent attractiveness of the industry.